That's not the monster we ordered - Fairgray, Richard 1985-; Jones, Terry 1942-2020 (Puffin, 2017)
"The Turner family has just got a monster, and the whole neighbourhood is in awe of his superhero stature, daredevil skill and all-round usefulness. Everyone wants their own monster. But sometimes the monster you order isn't necessarily the monster you get"--Publisher information
Picture story book for children
Keywords: Ungeheuer; Familie; Humor; Monsters / Fiction; Humorous stories; Picture books for children; Children's stories, New Zealand; Children's picture books; Humorous fiction; Juvenile works; Picture books; Bilderbuch